THE ROLE OF INTERNATIONAL RESEARCH IN THE DEVELOPMENT OF INTELLECTUAL ABILITIES IN PRIMARY SCHOOL MATHEMATICS EDUCATION - Baxronova Sarvinoz Akbar qizi (KONFERENSIYALAR, 2025)
Аnnotation. This article analyzes the issue of developing primary school students’ intellectual abilities through mathematics lessons. Based on international experience and research, effective approaches in this area are discussed, with particular focus on programs such as PISA, TIMSS, and CGI. The significance of methodological approaches that support intellectual development is examined from a scientific perspective